Changing causes of death in persons with haematological cancers 1975–2016 - Chen, Lezong; Zheng, Yongqiang; Yu, Kai; Chen, Shuzhao; Wang, Weida; Gale, Robert Peter; Liu, Ze-Xian; Liang, Yang (Leukemia, 2022)
Causes of death in persons with haematological cancers include the index cancer, a new cancer or a seemingly unrelated cause such as cardio-vascular disease. These causes are complex and sometimes confounded. We analyzed trends in cause of death in 683,333 persons with an index haematological cancer diagnosed in 1975–2016 reported in the Surveillance, Epidemiology and End Results dataset. Non-cancer deaths were described using standardized mortality ratios. The index cancer was the predominant cause of death amongst persons with plasma cell myeloma, acute lymphoblastic leukaemia and acute myeloid leukaemia. Non-cancer death was the major cause of death in persons with chronic lymphocytic leukaemia, Hodgkin lymphoma and chronic myeloid leukaemia, mostly from cardio-vascular diseases. The greatest relative decrease in index-cancer deaths was amongst persons with Hodgkin lymphoma, chronic myeloid leukaemia and chronic lymphocytic leukaemia, where the proportion of non-cancer deaths increased substantially. Changing distribution of causes of death across haematological cancers reflects substantial progress in some cancers and suggests strategies to improve the survival of persons with haematological cancers in the future.